Syngas Production by the Gasification of Bayah’s Coal over Ca(OH)2 and Na2CO3 catalyst - Heriyanto, Heri; Nahudin, Ahmad; Amyranti, Mutia; Firdaus, Mochamad Adha; Suhendi, Endang; Kosimaningrum, Widya Ernayati (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2020)
Official data of Indonesia’s coal reserve provided by government in 2014 approximately reached 104.8 billion tonnes. Bayah as a part of South Banten region has been stored quite amount of coal. Gasification is one solution to utilize Bayah’s coal potential. Coal Gasification is a conversion process of solid phase coal into synthetic gas mixture (CO, H2). Main reaction of the process involves Boundouard and Water-Gas-Shift reaction. The aim of experiment was to observes influence of several variables such as : Air Fuel Ratio (AFR), Temperature, and Catalyst at particular condition. Gasification process becomes beneficial when ratio of synthetic gas mixture (H2/CO) exhibits 2.0. Synthetic gas mixtures were analyzed by using gas chromatograph method. 300 grams of Bayah’s coal (14 – 18 mesh) were gasified in updraft type of fixed bed reactor using steam injection under Air Fuel Ratio varied between 1.5, 2.0, 2.5, temperature of 600°C, 700°C, 800°C and catalyst of Ca(OH)2 and Na2CO3 . Air Fuel Ratio of 1.5 and 800 with the help Ca(OH)2 catalyst tended to produce the optimum result for H2/CO ratio which obtained a value of 1.98. Synthetic gas composition at this variation reached 33.8% for Hydrogen and 17.1% for Carbon Monoxide.